UZBEKISTAN STATE WORLD LANGUAGE UNIVERSITY - Babayeva Irada Sabirovna (Journals Park Publishing, 2024)
There are some information about modern linguistics and its types and usage in languages. The importance of modern linguistics and the study of cognitive linguistics and its impact are explained. So, there are some strategies useful for teachers for organising their lessons effectively in linguistics.
Keywords: theoretical linguistics, language structure, phonology, syntax, semantics, psycholinguistics, language acquisition, typology.